HOW DIRECTORS' FOREIGN EXPERIENCE AFFECTS ESG's INFLUENCE ON TAX AVOIDANCE - Hartoni, Hartoni; Djakman, Chaerul Djusman (Widya Mandala Surabaya Catholic University, 2025)
Research Purposes. This study explores the empirical link between ESG performance and corporate tax avoidance, investigating the moderating role of directors with international experience in this relationship. Research Methods. The study analyzes ESG-focused data from Indonesian manufacturing firms, obtained from Thomson Reuters for the period 2017–2021, using a random-effects panel data regression model. Research Results and Findings. The results show the first hypothesis is not supported, revealing a positive relationship between ESG performance and tax avoidance. This implies that companies with high ESG scores may use these initiatives to manage reputational risks while engaging in tax avoidance. Conversely, the second hypothesis is supported, indicating that directors with international experience bring diverse perspectives, which enhance the negative relationship between ESG performance and tax avoidance, mitigating reputational and legitimacy risks.